A Robust Mixed‐Lanthanide PolyMOF Membrane for Ratiometric Temperature Sensing. Issue 48 (21st September 2020) - Feng, Tongtong; Ye, Yingxiang; Liu, Xiao; Cui, Hui; Li, Zhiqiang; Zhang, Ying; Liang, Bin; Li, Huanrong; Chen, Banglin
Abstract: Temperature sensors play a significant role in biology, chemistry, and engineering, especially those that can work accurately in a noninvasive manner. We adopted a photoinduced post‐synthetic copolymerization strategy to realize a membranous ratiometric luminescent thermometer based on the emissions of two lanthanide ions. This novel mixed‐lanthanide polyMOF membrane exhibits not only the integrity and temperature sensing behaviour of the Ln‐MOF powder but also excellent mechanical properties, such as flexibility, elasticity, and processability. Moreover, the polyMOF membrane shows remarkable stability under harsh conditions, including high humidity, strong acid and alkali (pH 0–14), which allowed the mapping of temperature distributions in extreme circumstances. This work highlights a simple strategy for polyMOF membrane formation and pushes forward the further practical application of Ln‐MOF‐based luminescent thermometers in various fields and conditions. Abstract : A polyMOF membranous luminescent thermometer is realized through the copolymerization of mixed‐lanthanide MOF with butyl methacrylate monomers. The membrane material not only exhibits ratiometric temperature sensing behavior in a flexible form but also shows remarkable stability under harsh conditions, making it a promising candidate for commercial applications.